Access to Plant Genetic Resources: Policies and Procedures - VANDANA TYAGI; PRAGYA RANJAN; PURAN CHANDRA; SUNIL ARCHAK; GYANENDRA PRATAP SINGH (Seed Research, 2026)
Exchange of plant genetic resources (PGR) is perhaps the simplest way to improve crops with new alleles. PGRs are exchanged and searched continuously for specific traits to improve crops in terms of yield and nutritional value. All countries are, therefore, interdependent on each other for sources of PGR, since many crops cultivated in a country have not originated there but are important for their food and nutritional security. Even biodiversity rich regions depend for their food production on crops/genotypes originated from other countries and this interdependence plays a very important role in the international collection and exchange of germplasm. Hence, every nation is concerned with acquisition of diverse and superior germplasm for conservation and utilization for crop improvement. The paper deals with the present status, policies and protocols relating to germplasm exchange for crop improvement in India.